ANALISIS PERILAKU BULLYING DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Hasanah, Hasanah; Tamarli, Tamarli; Saifuddin, Saifuddin; Taqiyah, Anisah; Nabila, Cut (Jurnal Dedikasi Pendidikan, 2025)
This bullying problem is a serious problem for the general public in general, because acts of violence in this day and age can happen anytime if we look at current technological developments, such as deviant behavior, bad ethics, morals and legal norms from the lightest. So the aim of this study is to analyze bullying behavior from the perspective of the Qur'an and Hadith, as we know that the Qur'an and hadith are the main sources for Muslims. The aim of this study is to look at the contents of the verses of the Qur'an and hadith regarding the explanation of bullying. This research method is a Library research method (library research) with qualitative descriptive-analytical analysis. The research results obtained in the Qur'an are the prohibition of insulting and criticizing others, the obligation to act fairly and reject acts of injustice, the prohibition of arrogance and belittling other people. Meanwhile, in the hadith of the Prophet Muhammad SAW it is explained that’s forbidden to mention other people’s shortcomings, to protect other people’s honor, to guard one’s tounge, andit’s forbidden to criticize other people’s physical appearance.